2020
DOI: 10.1093/annweh/wxaa062
|View full text |Cite
|
Sign up to set email alerts
|

(Mono-) Exposure to Naphthalene in the Abrasives Industry: Air Monitoring and Biological Monitoring

Abstract: Exposure to the bicyclic aromatic hydrocarbon naphthalene occurs in most cases along with other polycyclic aromatic hydrocarbons. Here we report from an investigation of 63 healthy, non-smoking male employees in the abrasives industry where naphthalene is the only relevant chemical exposure. Exposure assessment was performed using a combination of Air and Biological Monitoring over nearly a whole working week (Mo.–Th.). Air measurements were carried out during the shift on Thursday with the GGP mini-sampling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The goal was to evaluate the irritative and inflammatory effects of naphthalene on the eyes and the airways in exposed workers by using a series of various enpoint measures including self-reported work-related complaints and intensities of odor and irritation perception, nasal endoscopy, smell sensitivity, and inflammatory markers in serum, NALF and IS. A previous report on this cohort revealed that naphthalene in air was high and, specifically in working areas with direct handling of naphthalene, short-term peak concentrations up to 145.8 mg/m 3 could be observed (Weiss et al 2020 ).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The goal was to evaluate the irritative and inflammatory effects of naphthalene on the eyes and the airways in exposed workers by using a series of various enpoint measures including self-reported work-related complaints and intensities of odor and irritation perception, nasal endoscopy, smell sensitivity, and inflammatory markers in serum, NALF and IS. A previous report on this cohort revealed that naphthalene in air was high and, specifically in working areas with direct handling of naphthalene, short-term peak concentrations up to 145.8 mg/m 3 could be observed (Weiss et al 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…These assumptions have been confirmed specifically for our collective. In example, previously published data on exposure to naphthalene in the collective presented here (Weiss et al 2020) revealed high naphthalene shift concentrations up to 11.6 mg/m 3 with short-term peak concentrations up to 145.8 mg/m 3 (e.g., sieving pure naphthalene). In addition, biological monitoring revealed 1-and 2-naphthol concentrations in post shift urine up to 10.1 mg/L.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…According to some studies, the recommended biomonitoring of naphthalene exposure is 1and 2-naphthol in urine (Sams, 2017;Takeuchi et al, 2020;Weiss et al, 2020). However, there are several metabolites that can also be detected and used for biomonitoring of exposure.…”
Section: Introductionmentioning
confidence: 99%